2020
DOI: 10.1007/s11423-020-09833-x
|View full text |Cite
|
Sign up to set email alerts
|

Digital storytelling as a disciplinary literacy enhancement tool for EFL students

Abstract: This research compared the process of disciplinary literacy acquisition of students who experienced two different pedagogical approaches to learning science, technology, engineering and mathematics through astronomy (STEM-A). The objective of this study was to explore the impact of a digital storytelling (DST) educational technology intervention in a STEM-A context on the process of disciplinary literacy acquisition of students who were learning English as a foreign language (EFL). The research was designed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
(88 reference statements)
2
17
0
Order By: Relevance
“…Although it has been described by other definitions such as digital essays, digital documentaries, computer-based narrative, electronic memories, interactive storytelling, it is generally described based on the idea of combining the art of storytelling and a variety of multimedia elements, including graphics, sound, video, and web publishing (Daniels, 2013Doğan & Robin, 2008. The multimodal nature of the DST educational technology thus has the potential to be used to create an authentic learning context for all students, regardless of their background (Chubko, 2020). Smeda et al (2014) described DS as an innovative pedagogical approach that leads to deep and meaningful learning among students.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been described by other definitions such as digital essays, digital documentaries, computer-based narrative, electronic memories, interactive storytelling, it is generally described based on the idea of combining the art of storytelling and a variety of multimedia elements, including graphics, sound, video, and web publishing (Daniels, 2013Doğan & Robin, 2008. The multimodal nature of the DST educational technology thus has the potential to be used to create an authentic learning context for all students, regardless of their background (Chubko, 2020). Smeda et al (2014) described DS as an innovative pedagogical approach that leads to deep and meaningful learning among students.…”
Section: Introductionmentioning
confidence: 99%
“…This study is an extension of a previous study, the Indigenous Sky Stories program, conducted with Australian primary school students aged 10–12 years ( Ruddell et al, 2016 ). The conclusions reached in Chubko et al (2020) are that the creation of digital narratives promotes the literacy of scientific concepts, both in students who master the language of instruction, and in those who do not have this mastery, as demonstrated in an extensive case study, consisting of a sample of over 300 Australian and Kyrgyz students. The authors claim that the use of digital storytelling promoted creativity in constructing a digital narrative and the processes involved in this construction reduced the gap between native and non-native English students.…”
Section: Discussionmentioning
confidence: 96%
“…In another case study with a sample of 30 students from Kyrgyzstan aged between 12 and 16 years, Chubko et al (2020) used digital storytelling in science with non-native English students. This study is an extension of a previous study, the Indigenous Sky Stories program, conducted with Australian primary school students aged 10–12 years ( Ruddell et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research findings revealed that the components used in creating digital storytelling in language learning were in kind of brainstorming, research projects, writing a story, presentations performance, improving interpersonal skills, solving problem-based tasks, and technology skills (Timuc¸in, M., & Irgin, 2015). The results finding of a positive effect of digital storytelling on the students' knowledge of educational technology for EFL students' astronomy disciplinary literacy acquisition and non-EFL students' disciplinary literacy acquisition in STEM areas (Chubko, N et al, 2020), in addition, the results research from Balaman (2018) of his study found that digital storytelling writing instruction showed a significant effect in increasing students' narrative writing skills and digital storytelling can help teachers who want to find out the students' needs and expectations in the 21st-century composition classes.…”
Section: Introductionmentioning
confidence: 86%